Ideological Morality, Generality, and Particularity of Pip and Gatsby in Charles Dickens’ Great Expectations and F. Scott Fitzgerald’s The Great Gatsby - Shaghayegh Moghari (RIRAI Publisher, 2021)
‘Subaltern’ and ‘other’ are the two labels that are attributed to the weaker members of the society and the whole world in general sense in terms of color of the skin, the gender, the financial conditions, and the social status. This study attempts hard to defend the characters of Pip and Gatsby who were considered as ‘subaltern’ and ‘other’ by the unjust society and system around them and as a result, though they attained the wealth they always dreamed of, they failed to attain a good life that they deserved. Even Pip, who succeeded in marrying his beloved, cannot be regarded as a lucky guy because he was able to have her only after a divorce that she experienced in her first marriage; so, this cannot be taken as a success for Pip. The following issues will be expanded and examined in details to clarify the way the present researcher has always tried to encourage the world around her to treat the weaker better, and also to convert the world into a better place to live by enjoying equal rights for all: Gayatri Spivak, the voice of the voiceless, ‘Other’ and ‘subaltern’ in Pip and Gatsby, and the unfair oppression of the world against the so called ‘other’ and ‘subaltern.’